Devising new technique as an emerging trend to perform Physics experiment in a simpler and unconventional manner - Chawla, Swati; Mahajan, Archie; Malik, Harsh (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Education is a critical component that contributes extensively in the human development indices. The educational pedagogies must be dynamic and be able to create independent learners. Physics is stimulating and the world today increasingly depends on it. Sadly, many students feel uncomfortable with the subject and are skeptical about pursuing it as a career option in their later life. Hence, it is of utmost importance that we dispose of these inhibitions by bringing in new, out of the box techniques, which are in accordance with educational standards, the world over. Along with this, these techniques will also serve as the new emerging trend in the field of Physics. Usually, school students are required to do a certain number of experiments specified in syllabus and the experiments are performed by the students in a guided manner without putting much thought inthe extrapolation of concepts or finding alternative methods of determining the same physical quantity by simpler and innovative method. The experiment being presented in this paper is based upon the above philosophy, wherein different magnetic fields B1, B2, B3,….. at the centre of circular coil are produced using different values of current in a coil (keeping the direction of current constant) and by reversing current (keeping magnitude of current constant). A small magnet is made to vibrate in combined magnetic fields B due to current and Earth’s magnetic field H. Vibration of magnet in a magnetic field and production of magnetic field perpendicular to the plane of coil due to current are the key concepts used in the experiment. In this paper, for determining the horizontal component of earth’s magnetic field (H) and hence magnetic moment of magnet (M), a set of new equations has been derived which suggest simple method of determination of H and M, which are the backbone of the experiment. The value of H using first method, when direction of current is reversed (magnitude remains same) comes out to be H(experimental) = 3.15E-05 and using second method, when changing currents is applied (direction remains same), H(experimental) = 3.02E-05. The theoretical value of H is 3.20E-05, which clearly indicates that both, theoretical and experimental values are nearly same. Thus, this approach will serve as a catalyst in the process of concept-building since it provides a precedent, for adopting this technique for other experiments as well. This new methodology will henceforth enhance the experience hands-on experiments, and impart ever-lasting learning in the field of Physics.